KEPENTINGAN EKONOMI POLITIK INDONESIA KELUAR DARI KEANGGOTAAN OPEC PADA TAHUN 2016 - Muhammad Akbar; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research would explain about the importance of Indonesia out of OPEC membership in 2016. The release of Indonesia from OPEC membership due to OPEC’s policy that regulate the quota of production of its member states about 5% of the total production of its member countries, the aim is to raise world oil prices. The OPEC’s policy is not in line with Indonesia's national interests. Indonesia is asked to reduce the production by 5% or about 37,000 barrels per day not in accordance with Indonesia's national interests. Because in terms of revenue of the State Budget Indonesia is still in a period of improvement.In discussing the problems of Indonesian political economy interest out of OPEC membership in 2016, the author uses an explanotary qualitative research methodology, the data collection technique by library research are derived from sources literary books, published magazine, journals, and scientific articles. The perspective used is mercantilism that see the state’s role in regulating its economy The theory used is the theory of International Political Economy, and the use of concept of national interest. Indonesia's decision to leave OPEC membership because production cuts of OPEC are not beneficial to Indonesia as Indonesia has become an importer country with production cuts which is determined by OPEC will certainly harm for Indonesia because the domestic demand of oil continues to rise and Indonesia will continue to import and can not increase the export. The release of Indonesia from OPEC membership has no significant effect on Indonesia's bilateral relations with other countries, especially OPEC oil producing countries, Indonesia in the near future will strengthen cooperation in the field of oil and gas with Iran and the relationship of Indonesia Saudi Arabia keep running until the moment this.Key Words: OPEC Policy, The National interest of Indonesia , Mercantilist Perspective